Metaphors of "The Female" in Malay movies / Fuziah Kartini Hassan Basri and Faridah Ibrahim - Hassan Basri, Fuziah Kartini; Ibrahim, Faridah (Fakulti Seni Persembahan & UPENA, 2004)
This article discusses metaphors of "the female" in some selected Malay movies of the 1950s and 2000s spurned from two qualitative analyses of gender images in Malay movies. These studies demonstrated that Malay movies have dialogues that are colored by metaphors and that they function to construct certain images about women which are not always positive. At a time when women are contributing much towards society's progress, some of the metaphors are irrelevant; they only perpetuate the ideology of male dominance-female submissiveness. From a communication perspective, the use of these metaphors in a medium deemed so influential to young minds, is culturally detrimental. We need to continuously advocate a change so that we can ultmmtely practise the humanistic view of gender equality in our daily lives. Perhaps this may pjppOigatg male respect for the female, thus help eliminate crime and violence against women.